2006
DOI: 10.2527/jas.2005-676
|View full text |Cite
|
Sign up to set email alerts
|

Effect of timing of feeding a high-concentrate diet on growth and attainment of puberty in early-weaned heifers1

Abstract: Precocious puberty (<300 d of age) can be successfully induced in a majority of heifers with early weaning and continuous feeding of a high-concentrate diet. The objective of this experiment was to determine the relative effects of timing of feeding a high-concentrate diet on age at puberty in early-weaned heifers. Sixty crossbred Angus and Simmental heifer calves were weaned at 112 +/- 2 d of age and 155 +/- 3 kg of BW and were fed a receiving diet for 2 wk. Heifers were blocked by age and BW, and assigned ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
57
1
18

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 19 publications
10
57
1
18
Order By: Relevance
“…The presence of PPARG and its 23 targets in common with ESRRG in our network was evidence for the AWM capturing known biology. There are demonstrated associations between energy balance and reproduction (37,38). If fat deposition traits were excluded from our analysis, this PPARG and ESRRG link could have been missed.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of PPARG and its 23 targets in common with ESRRG in our network was evidence for the AWM capturing known biology. There are demonstrated associations between energy balance and reproduction (37,38). If fat deposition traits were excluded from our analysis, this PPARG and ESRRG link could have been missed.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement, Larson et al (2011) reported increased body weight after corn residue administration for winter grazing. Early post-weaning growth has a more profound effect on reproductive success in the first breeding season, indicating that weaning weight has a major impact on timing of puberty (Roberts et al, 2009) and can be consistently induced by a high-energy diet of beef heifers (Gasser et al, 2006). Banta et al (2005) observed that two-year-old cows subjected to early weaning showed 92% of estrus appearance and 71% of conception rates, demonstrating that increasing energy intake of cows through early weaning should result in decreased postpartum interval and increased pregnancy rates.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting our rationale, Moriel et al (2014b) reported reduced age and BW at puberty in heifers weaned at 72 days of age and fed a high-concentrate diet for 90 days compared with forage-fed cohorts weaned at 252 days of age. Gasser et al (2006) observed that beef heifers weaned at 112 days of age and fed a corn-based diet for 10 week reached puberty sooner than forage-fed contemporaries. However, the similar rate of puberty attainment between MI and CON heifers in the present experiment do not support our hypothesis, but parallels the similar subcutaneous fat accretion and plasma concentrations of IGF-I and leptin between treatments during the peripubertal period (Schillo et al, 1992;Williams et al, 2002;Cooke et al, 2008).…”
mentioning
confidence: 98%
“…Perhaps the length and rate of supplementation utilized herein were insufficient to impact the aforementioned variables, despite the long-term increase in hepatic IGF-I and adipose PPARγ mRNA expression that suggests a metabolic imprinting effect (Du et al, 2010). Heifers utilized by Gasser et al (2006) and Moriel et al (2014b) consumed a corn-based diet for, respectively, 10 week at 2.5% to 3.0% of heifer BW or 90 days at 3.5% of heifer BW. In the present experiment, MI heifers consumed a free-choice corn-based supplement for 50 days at 0.83% of heifer BW.…”
mentioning
confidence: 98%